The Development of Electronic Banking Services in Poland in the Era of the COVID-19 Pandemic using the Example of PKO Bank Polski - Feruś Anna (Folia Oeconomica Stetinensia, 2022)
Research background: The COVID-19 pandemic has changed consumer preferences and their use of banking services. Consequently, the propensity of bank customers to use electronic banking has increased. Banks, in order to meet customer expectations, develop and improve the most popular channels of distribution of their services, offering increasingly advanced technological solutions that provide the customer with a high level of security.